Psychotherapy Reduces Self Esteem Scizophrenic Patients: Literature Review - Maulana, Indra; Shalahuddin, Iwan; Eriyani, Theresia (Universitas Aisyah Pringsewu, 2021)
Low self-esteemis all the thoughts, beliefs and beliefs that an individual knows about him self and affects his relationships with others. This study aims to determine what interventions can be given to over come chronic low self-esteem problems. The method used in this research is descriptive review by conducting literature reviews both from within and outside the country. Literature searches were carried out through several databases, namely Google Scholar, Pubmed, and Science Direct. The strategy used to search the literature is touse the keyword